STUDI KASUS: ASUHAN KEBIDANAN KOMPREHENSIF PADA NY. S DI PUSKESMAS WATUMALANG WONOSOBO - Solekhah, Himatul Latif Makna; Tyarini, Indrawati Aris; Nurdiani, Nurdiani; Nugraheni, Nazilla (Jurnal Ilmiah Kesehatan, 2024)
The aim of this research was for the author to be able to implement comprehensive midwifery care according to midwifery service standards for pregnant women, maternity, BBL, neonates, postpartum and family planning with SOAP documentation. The method for taking this case was a descriptive approach and midwifery management using Continuity of Care for Mrs. S aged 36 years at the Watumalang Community Health Centerand KRT Hospital. Setjonegoro Wonosobo start March 14, 2024 - April 27, 2024.During the implementation, 3 pregnancy assessments were carried out and the problem of pregnant women with obesity was found, during delivery the mother experienced problems with rupture of cloudy membranes accompanied by PU (+), in BBL and neonates problems were found asphyxiated birth babies then hypoglycemia and ineffective breastfeeding occurred, in 4 No problems were found during postpartum visits, and the mother chose to use implant birth control. Midwifery care for pregnant women with a high risk of pregnancy ≥35 years accompanied by obesity carried out on Mrs. S, 36 years old, has received treatment and management according to midwifery care standards.